Simulation and Hardware Implementation of Shunt Active Power Filter Based on Synchronous Reference Frame Theory - Karthikrjan Senthilnathan; Iyswarya Annapoorani; S. Ravi (Universitas Ahmad Dahlan, 2018)
This paper describes about the Shunt Active Power Filter (SAPF) for the elimination of the current harmonics in the line side. The Active Power Filter is based on the Voltage Source Inverter (VSI) topology. The Synchronous Reference Frame (SRF) theory based control strategy is utilized for SAPF. The SAPF has the better performance for compensation of harmonics. The simulation of shunt active power filter is performed in MATLAB/Simulink. The SAPF is implemented in hardware protptype with ATMEGA 8 Microcontroller. The Simulation and Hardware result shows that the current harmonics are eliminated in the system.